Brugada syndrome unmasked by dengue fever - Lokesh Koumar Sivanandam; Hima Bindu R. Basani; Vivek Sanker; Shamal Roshan S; Marah Hunjul; Umang Gupta (Clinical Case Reports, 2023)
Key Clinical Message Understanding the circumstances, leading to unmasking of hidden Brugada syndrome is essential for the practicing clinician and the patients so that they are informed adequately to seek prompt medical attention. Abstract Brugada syndrome is a genetic arrhythmia syndrome characterized by a coved type of ST‐segment elevation in the ECG. The patients are usually asymptomatic, with unmasking of the disease under certain conditions. We are reporting the case of a patient diagnosed with Brugada syndrome, which was unmasked during an attack of dengue fever.